Assessing carbon lock-in. (25th August 2015) - Erickson, Peter; Kartha, Sivan; Lazarus, Michael; Tempest, Kevin
Abstract: The term 'carbon lock-in' refers to the tendency for certain carbon-intensive technological systems to persist over time, 'locking out' lower-carbon alternatives, and owing to a combination of linked technical, economic, and institutional factors. These technologies may be costly to build, but relatively inexpensive to operate and, over time, they reinforce political, market, and social factors that make it difficult to move away from, or 'unlock' them. As a result, by investing in assets prone to lock-in, planners and investors restrict future flexibility and increase the costs of achieving agreed climate protection goals. Here, we develop a straight-forward approach to assess the speed, strength, and scale of carbon lock-in for major energy-consuming assets in the power, buildings, industry, and transport sectors. We pilot the approach at the global level, finding that carbon lock-in is greatest, globally, for coal power plants, gas power plants, and oil-based vehicles. The approach can be readily applied at the national or regional scale, and may be of particular relevance to policymakers interested in enhancing flexibility in their jurisdictions for deeper emissions cuts in the future, and therefore in limiting the future costs associated with 'stranded assets'.